Self-Efficacy, Self-Compassion, and Dietary Compliance Of Diabetes Mellitus Patients - Jek Amidos Pardede; Galvani Volta Simanjuntak; Marthalena Simamora; Melda Parapat (TOUR HEALTH JOURNAL, 2022)
Background: Diabetes   Mellitus   is   a   disease   that   cannot   be cured, but it can be controlled so that patients can live their lives well. One of the ways to control this is by adjusting the diet. Purpose: The purpose of this study was to determine the relationship   between   self-efficacy and self-compassion with dietary compliance of diabetes mellitus patients. Method: The research method used  was  correlation  analytic with  a  cross  sectional  approach. The  population  of  this  study  is diabetes mellitus outpatients  at RSUD  Dolok Sanggul. Sample was  taken  by  accidental  technique  of  50  people. Data  collection using a   questionnaire and   data   analysis using spearman correlation test with a significance level of 0.05. Result: The  results showed  that  the  majority  of  respondents had  low  self-efficacy as many  as 33  people (66%),  the majority of respondents had low self-compassion as many as 38 people(76%) and the majority of respondents diet  compliance  was low  as  many  as  35  people  (70%).  The  results  of the  Spearman correlation test between self-efficacy (p0,001; r 0,625) and self-compassion (p0.001   ;   r   0,734)   with dietary   compliance   of diabetes mellitus patients. Conclusion: There is a strong relationship between self-efficacy and self-compassion witt dietary compliance of diabetes mellitus patients. The better the self-efficacy and self-compassion,  the  more  obedient  the  diabetic  patient  will  be  in implementing the diet program.